Program Orang Tua Mengajar sebagai Bentuk Parenting Sekolah pada Pendidikan Anak Usia Dini - Assyifa’u Nurul Istiqomah; Endah Tejaningsih (Jurnal Pendidikan Anak Usia Dini dan Kewarganegaraan, 2026)
Early childhood education requires collaboration between schools and parents to support children’s development optimally. One form of parental involvement in learning is through the parent teaching program, in which parents participate as “guest teachers” in the classroom. This study aimed to describe the implementation of the parent teaching program and its contribution to early childhood development at TK Arrohmanul Huda Winong. The study employed a qualitative method with a case study design. Data were collected through observation, interviews, and documentation from September 2025 to April 2026. The research subjects included the principal, classroom teacher, and parents of students. The findings revealed that the parent teaching program was conducted once a month based on agreements between the school and parents. The activities included introducing professions, cooking, sewing, gardening, and other educational activities. The program showed a positive influence on children’s development, especially in cognitive and socio-emotional aspects. Children became more active, confident, enthusiastic, and better able to understand learning materials through direct experiences and practical activities. In addition, the program strengthened the relationship between schools and families in supporting the learning process of early childhood education. However, the implementation of the program still faced challenges in scheduling because most parents were workers, so the activities were more often conducted at the end of the week. This study indicates that parental involvement in classroom learning can be an effective strategy for creating more interactive, contextual, and meaningful learning experiences for young children.